Zrożnicowanie plio-plejstoceńskich Hominidae III. Konsekwencje taksonomiczne i antropogenetyczne - Kaszycka, Katarzyna A. (Polskie Towarzystwo Antropologiczne, 1986)
This work presents the final part of a cycle of articles among which the two latter ones discussed the morphology, ecology and sexual dimorphism of early hominids called Australopithecines. The present part evaluates two different interpretations of hominid phylogeny: multi-species hypothesis and the single species one. The proposals of R. Broom; Louis, Mary and Richard Leakey; J. Robinson, D. Pilbeam and M. Zwell; and D. Johanson and T. White have been discussed. Attention has been concentrated on cases of unjustified multiplication of terminology (Table 1), essential erroneous interpretations (e.g. Zinjanthropus), and fluctuations of taxonomic views, the dietary hypothesis (Table 2, Fig. 1), conceptions following from the discovery of Homo habitis (Fig.6), and the discoveries from Hadar and Laetoli (Fig.7,8). The above hypotheses are opposed by the proposal of M. Wolpoff and C. Brace basing mainly on the data about sexual dimorphism of Piio-Pleistocene hominids, a high allometric variability, réévaluation of J. Robinson’s hypothesis and on the rejection of the taxon Homo habilis. In the discussion the author deals more extensively with the single species hypothesis, indicating its weak points (option in the use of metric data - Table 7, and interpretation through allometry) but pointing out its merits as well. In the conclusion the author states that the discussion concerning the phylogenetic systematics of Plio-Pleistocene hominids has not been terminated yet. In the present state of studies the most convincing seems to be the hypothesis of two lineages proposed among others by Pilbeam and Zwell, and Johanson and White. According to them the direct ancestor of the modern man is the form of Homo habilis, while Australopithecus robustus represents a sidebranch of the phylogenetic tree. The problem which of the Plio-Pleistocene forms was the common ancestor of the mentioned lineages requires a solution.
Differentiation of plio-pleistocene Hominids. III. Taxonomic and anthropogenetic consequences